Reduced Th22 cell proportion and prevention of atopic dermatitis in infants following maternal probiotic supplementation. Issue 8 (21st April 2017) - Rø, A. D. B.; Simpson, M. R.; Rø, T. B.; Storrø, O.; Johnsen, R.; Videm, V.; Øien, T.
Summary: Background: In the randomized, controlled study Probiotics in the Prevention of Allergy among Children in Trondheim (ProPACT), maternal probiotic supplementation reduced the incidence of atopic dermatitis (AD) in the offspring. In the current study, we hypothesized that the effect was mediated by a shift in the T helper (Th) cells in the children. Objective: To examine whether Th cell proportions were affected by maternal probiotic supplementation and thus could mediate the preventive effect of probiotics on AD. Methods: A total of 415 pregnant women were randomized to ingest a combination of Lactobacillus rhamnosus GG (LGG), Bifidobacterium animalis subsp. lactis Bb‐12 (Bb‐12) and Lactobacillus acidophilus La‐5 (La‐5) or placebo, and their offspring were assessed for AD during the first 2 years of life. Peripheral blood collected at 3 months of age was analysed for regulatory T cells (n=140) and Th subsets (n=77) including Th1, Th2, Th9, Th17 and Th22. Results: The proportion of Th22 cells was reduced in children in the probiotic group compared to the placebo group (median 0.038% vs 0.064%, P =.009). The difference between the probiotic and placebo groups was also observed in the children who did not develop AD during the 2‐year follow‐up. The proportion of Th22 cells was increased in children who developed AD compared to the children who did not develop AD (0.090% vs 0.044%, P <.001). Mediation analysis indicated that the preventive effect of probiotics was partially mediated through the reduction in Th22 cells. Conclusion: Perinatal maternal probiotic supplementation with a combination of LGG, Bb‐12 and La‐5 reduced the proportion of Th22 cells in 3‐month‐old children. This may partially explain the preventive effect of probiotics on AD.